EXPONENTIAL FUNCTIONS - Kamalova Hillolakhan Solijonovna (Web of Journals Publishing, 2023)
This article delves into the realm of exponential functions, a fundamental concept in mathematics and science. Exponential functions play a pivotal role in various disciplines, from finance to biology, demonstrating their versatility and significance. The article provides a comprehensive overview, analyzing existing literature, exploring methodologies, presenting results, and offering insightful discussions on the implications and applications of exponential functions.
Keywords: Exponential functions, mathematical modeling, growth and decay, applications, literature review, methodology, results, discussion, conclusions.